Development of hydropower sustainability assessment method in Malaysia context - Faiz, Mohd Turan; Kartina, Johan; Nur Atiqah, Omar (IOP Publishing, 2018)
Nowadays, sustainability is becoming one of the crucial requirement to business success today. This requirement is strongly supported by Bursa Malaysia. In their webpage, they stated that an entire way to business management, incorporating economic, environmental, social and governance considerations alongside financial ones, will serve as a sound business model that supports business continuity and long term value creation for stakeholders and society at large (Bursa Malaysia website, 21th April 2016). This proved that companies need to take sustainability as one of their aspect performance as well as an energy company. Apart from that, energy companies in Malaysia are facing problems as there is still no systematic assessment of sustainability. Before this, Malaysia energy companies assess their large projects based on Environmental Impact Assessments (EIAs) requirement. However, the EIAs mostly covers the environmental issues related to the projects. The EIAs give less attention to the social aspects and economical aspects. In addition, there are still not many companies comply all the three aspects together. So, this study is to help the energy companies to discover the systematic assessment of sustainability. In developing sustainable project, they need to include many criteria that cover the environmental, economic and social aspects at all stages. Thus, the new version of Systematic Sustainability Assessment (SSA) that apply the Hydropower Sustainability Assessment Protocol (HSAP) is used as a guideline to achieve sustainability in Malaysia energy companies. This tool will guide the energy company on how to assess the sustainability in their project and see the performance of the project.